2020
DOI: 10.31893/jabb.20028
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of heat stress in broiler chicken using turmeric (Curcuma longa) - a short review

Abstract: Heat stress is one of the most crucial issues in broiler production, particularly in tropical regions. Thermal stress may pose several problems related to growth, feed intake, nutrient utilization, physiological condition, immune function, intestinal ecology, and morphology as well as the antioxidant system in the body of chickens. Turmeric (Curcuma longa) is rich in curcumin, which can serve as an antioxidant. Being part of the nutritional interventions, treatment using turmeric has been documented to allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…As a result, our findings showed that PSM and SPSM might help broilers cope with stressful conditions. Similar to creatinine, the ALT levels often rise in broilers during stressful circumstances, indicating oxidative stress and injury to internal organs such as the liver and kidney (Sugiharto, 2020b). The blood levels of ALT was lower (P<0.05) in broilers fed SPSM at 1 and 2.5% of feed in this study (Table 6).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…As a result, our findings showed that PSM and SPSM might help broilers cope with stressful conditions. Similar to creatinine, the ALT levels often rise in broilers during stressful circumstances, indicating oxidative stress and injury to internal organs such as the liver and kidney (Sugiharto, 2020b). The blood levels of ALT was lower (P<0.05) in broilers fed SPSM at 1 and 2.5% of feed in this study (Table 6).…”
Section: Resultsmentioning
confidence: 52%
“…Creatinine has traditionally been used as a marker for protein metabolism. Increased muscle protein catabolism and consequently greater amounts of creatinine in broiler circulation are generally associated with increased corticosterone levels during stressful situations (Sugiharto, 2020b). In this investigation, feeding PSM or SPSM to broilers resulted in reduced (P<0.05) levels of creatinine in their serum when compared to control.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…These bioactive compounds have numerous biological activities such as antioxidant, antiviral, anti-inflammatory, hepatoprotective, immunostimulatory, and antimicrobial (Abdel-Daim et al 2019;Abdel-Moneim et al 2021a;Abedin and Taha, 2008;Aladaileh et al 2020). A growing body of literature has attributed these medicinal properties of S. platensis to their ability to modulate cytokines and antibodies production, inhibit lipid peroxidation, enhance disease resistance, and scavenge free radicals effectively, thereby improving the productivity and profitability of the poultry industry (Abdel-Daim et al 2019, 2020Abdelkhalek et al 2015;Aladaileh et al 2020;Evans et al 2015;Farag et al 2016). Taken together, these different mechanisms qualify S. platensis to be used to mitigate the deleterious impacts of heat stress in poultry (Abdel-Moneim et al 2021c).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary manipulation is a practical way to alleviate detrimental consequences of HS on broilers currently. These supplemental substrates include plant extract (Zhang et al 2018a;Sugiharto 2020), vitamin (Zeferino et al 2015;Abdelhameed et al 2019), mineral (Habibian et al 2015), probiotic (Al-Fataftah and Abdelqader 2014), prebiotic (Cheng et al 2019b), and synbiotic (Mohammed et al 2018). Synbiotic, a mixture of probiotic and prebiotic, beneficially affects the host by improving survival and implantation of health-promoting bacteria in the gastrointestinal tract (Pandey et al 2015;Krumbeck et al 2016).…”
Section: Introductionmentioning
confidence: 99%